Traditional Rainwater Management (Haveli cultivation) for Building System Level Resilience in a Fragile Ecosystem of Bundelkhand Region, Central India - Singh, Ramesh; Akuraju, Venkataradha; Anantha, K. H.; Garg, Kaushal K.; Barron, Jennie; Whitbread, Anthony M.; Dev, Inder; Dixit, Sreenath (Frontiers in Sustainable Food Systems, 2022)
This article presents the evidence on how the traditional rainwater management system (haveli system) has contributed toward rehabilitating degraded landscapes and changing them into a productive form in Bundelkhand region of Central India. The haveli system was the lifeline of the region for water security for the last 300 years. Farmers (~1–5%) situated at the upstream of the landscape were harvesting surface runoff in their fields during monsoon by constructing earthen embankments along with provision to drain out water after receding of the monsoon. Farmers traditionally cultivated only during the post-monsoon period, using residual soil moisture along with supplemental irrigation from shallow dug wells. However, this system became defunct due to apathy and poor maintenance. The traditional design of the havelis were also often malfunctioning due to new rainfall patterns and storm events. Farmers are facing new need for haveli rejuvenation and the traditional design and knowledge calls for new innovations, particularly from research and external expertise. In this context, ICRISAT and consortium partners have introduced an innovative approach for haveli rejuvenation by constructing masonry core wall along with outlet at a suitable location. Totally 40 haveli structures were constructed between 2010 and 2021 across seven districts of Bundelkhand region. One of the pilot sites (i.e., Parasai-Sindh) was intensively monitored in order to capture the landscape hydrology, change in land use, cropping intensity and crop productivity, between 2011 and 2017. Out of 750 mm rainfall received during July and September, generated surface runoff is about 135 mm (18% of rainfall) on average. However, rainfall below 450 mm (dry years) rarely generates surplus water as most of the rainfall received in such years are absorbed within the vadose zone, whereas, wet years with over 900 mm rainfall, generate runoff of about 250–300 mm (~30–35%). Rejuvenation of the haveli system created an opportunity to harvest surface runoff within farmers' fields which helped to improve groundwater levels in shallow dug wells (additionally by 2–5 m hydraulic head) which remained available during the following years. This has increased cropping intensity—by converting about 20% of permanent fallow lands into productive agriculture lands—and ensured irrigation availability especially during the critical crop growth stage. This enhanced land and water use efficiency of the system and increased household net income by two to three folds as compared to the baseline status. This article further establishes the link between landscape rejuvenation through haveli system, groundwater resource availability, production system and household income in the fragile ecosystem of Central India. The results are helpful for various stakeholders so that they can take informed decisions on sustainable natural resource management.